Generating Multicompartmental 3D Biological Constructs Interfaced through Sequential Injections in Microfluidic Devices. Issue 10 (7th March 2017) - Ugolini, Giovanni Stefano; Visone, Roberta; Redaelli, Alberto; Moretti, Matteo; Rasponi, Marco
Abstract : A novel technique is presented for molding and culturing composite 3D cellular constructs within microfluidic channels. The method is based on the use of removable molding polydimethylsiloxane (PDMS) inserts, which allow to selectively and incrementally generate composite 3D constructs featuring different cell types and/or biomaterials, with a high spatial control. The authors generate constructs made of either stacked hydrogels, with uniform horizontal interfaces, or flanked hydrogels with vertical interfaces. The authors also show how this technique can be employed to create custom‐shaped endothelial barriers and monolayers directly interfaced with 3D cellular constructs. This method dramatically improves the significance of in vitro 3D biological models, enhancing mimicry and enabling for controlled studies of complex biological districts. Abstract : A technique for molding and culturing 3D spatially controlled composite cellular constructs and organs‐on‐chip directly within microfluidic devices is presented. The authors show how this technique is employed for shaping, without the use of confining structures, stacked and flanked hydrogel constructs, or endothelial barriers lining hydrogel constructs.